Formation of Novel Octuplex DNA Molecules from Guanine Quadruplexes. Issue 8 (21st January 2021) - Katrivas, Liat; Fardian‐Melamed, Natalie; Rotem, Dvir; Porath, Danny; Kotlyar, Alexander
Abstract: Guanine quadruplex (G4)‐DNA structures have sparked the interest of many scientists due to their important biological roles and their potential use in molecular nanoelectronics and nanotechnology. The high guanine content in G4‐DNA endows it with mechanical stability, robustness, and improved charge transport properties—attractive attributes for a molecular nanowire. The self‐driven formation of a novel G4‐DNA‐based nanostructure, coined guanine octuplex (G8)‐DNA, is reported herein. Atomic force microscopy and scanning tunneling microscopy characterization of this molecule reveal its organized coiled‐coil structure, which is found to be stable under different temperatures and surrounding conditions. G8‐DNA exhibits enhanced stiffness, mechanical and thermodynamic stability when compared to its parent G4‐DNA. These, along with its high guanine content, make G8‐DNA a compelling new molecule, and a highly prospective candidate for molecular nanoelectronics. Abstract : The self‐driven formation of a novel type of DNA‐based molecule, with the highest number of guanines per cross section, is reported. Atomic force microscopy, scanning tunneling microscopy, and CD spectroscopy of guanine octuplex (G8‐) DNA reveal its organized, mechanically and thermodynamically stable, of high guanine content, coiled‐coil structure—which make it a prospective candidate for molecular nanoelectronics.